Anti-Corruption Policy of The Republic of Korea: History of Formation and Modernity - Buronov Shakhboz Ruzikul Ugli (Indonesian Journal Publisher, 2025)
According to a number of domestic and foreign experts, the anti-corruption legislation of the Republic of Korea is recognized as one of the most advanced in the world. In this regard, in this article, the author attempts to reflect the results of his scientific research on the anti-corruption legislative provisions of the Republic of Korea. The basis of this scientific work is a meaningful analysis of the legislative acts of this country in the field of legal regulation of combating corruption. In the course of the research, the author found that the Republic of Korea has adopted many legal preventive legislative measures aimed at combating corruption. The study of a wide range of regulatory legal acts aimed at combating corruption in the country under consideration allowed the author to draw conclusions regarding the sufficiently advanced legislative foundations of the anti-corruption legislation of the Republic of Korea